Humility as enlightened leadership: a Chinese perspective. Issue 3 (9th April 2019) - Xu, Feng; Xu, Benhua; Anderson, Verl; Caldwell, Cam
Abstract : Purpose: Humility as an important factor for leaders was identified by Collins (2001) and his colleagues in an extensive research project about the leadership qualities of the leaders of companies that transitioned from "good" to "great." This paper is an empirical study of six factors closely associated with humility and leadership and the purpose of this paper is to identify how Chinese business students and Chinese employees perceive the importance of six factors associated with humility as enlightened leadership. Design/methodology/approach: This paper summarizes recent research about humility and leadership and suggests seven hypotheses about the importance of six factors associated with humility as enlightened leadership. Findings: This study confirms that Chinese respondents affirmed the value of all six factors and identified the statistical significance of three of the factors studied. Research limitations/implications: A limitation of this study is that it is exploratory in nature and contained many factors that made conducting factor analysis indeterminable. The practical implications of this study are that it provides confirming information about understanding the value system and priorities of Chinese employees and future workers when multi-national companies interact with Chinese partners. Originality/value: This study provides valuable information about the six factors associated with humility as enlightened leadership. This study is the first of its kind that empirically tests Chinese attitudes associated with humility and leadership.